Novas abordagens na produção de anticorpos monoclonais e caracterização de epitopos lineares e conformacionais de metaloproteases de venenos de serpentes de classe P-I - Francisco Santos Schneider (2014)
This work is presented in format of three published manuscripts in indexed international journals. Each article is located in one separated chapter within RESULTS. Once each paper presents its own ABSTRACT, here we briefly describe the content of the chapters: The first article (Artigo 1 – The novel metalloproteinase atroxlysin-I from Peruvian Bothrops atrox (Jergón) snake venom acts both on blood vessel ECM and platelets) describes for the first time the purification and biochemical characterization of a P-I class metalloproteinase from Bothrops atrox venom. In the second chapter of our RESULTS (Artigo 2 – Use of a Synthetic Biosensor for Neutralizing Activity-Biased Selection of Monoclonal Antibodies Against Atroxlysin-I, an Hemorrhagic Metalloproteinase from Bothrops atrox Snake Venom), we produce monoclonal antibodies against atroxlysin-I using a new functional method for the selection of clones able to produce neutralizing monoclonal antibodies, as well as their immunochemical characterization and the identification of continuous epitopes of atroxlysin-I. Finally, the third manuscript presented in our RESULTS (Artigo 3 – Mimotopes of mutalysin-II from Lachesis muta snake venom induce hemorrhage inhibitory antibodies upon vaccination of rabbits) characterizes conformational epitopes recognized by the monoclonal antibody LmmAbB2D4 against mutalysin-II. Mimotopes of mutalysin-II was identified using the phage display and SPOT synthesis techniques. Every article presents an individual discussion. At the end of the last manuscript a comprehensive and integrative discussion of the three papers is presented.